A lithium ion battery

By using silicon-based materials and specific non-aqueous electrolyte components in lithium-ion batteries, the silicon element content and compaction density are controlled, and the battery deterioration problem caused by volume changes in lithium-ion batteries at high temperatures is solved, achieving high energy density and long The balance of life spans significantly improves high-temperature storage and cycling performance.

CN117497825BActive Publication Date: 2025-01-14SHENZHEN CAPCHEM TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311673640.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-07
Publication Date
2025-01-14
Estimated Expiration
2043-12-07

AI Technical Summary

Technical Problem

Under high temperature conditions, the volume changes of the silicon-based negative electrode active material lead to rupture of the SEI film and decomposition of the electrolyte solvent, which affects the battery cycle characteristics and life, making it difficult to achieve both high energy density and long life.

Method used

Using a negative electrode containing a silicon-based material, fluorovinyl carbonate and a silane compound of structural formula 1 are added to the nonaqueous electrolyte. By controlling the content and compaction density of silicon elements, the ratio of fluorovinyl carbonate and silane compound is formed. The stable solid electrolyte membrane inhibits volume changes and side reactions and improves the high-temperature storage and cycling performance of the battery.

Benefits of technology

It significantly improves the energy density and high-temperature cycle life of lithium-ion batteries, extends the cycle life of the negative electrode, reduces the high-temperature storage gas production and battery impedance, and ensures the stability and performance of the battery under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDA0004594080020000011
    Figure FDA0004594080020000011
  • Figure FDA0004594080020000031
    Figure FDA0004594080020000031
  • Figure FDA0004594080020000032
    Figure FDA0004594080020000032
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium ion batteries, and specifically to a lithium ion battery with excellent high-temperature storage and high-temperature cycle performance. The lithium ion battery comprises a positive electrode, a negative electrode and a non-aqueous electrolyte; the negative electrode comprises a negative electrode material layer comprising a silicon-based material; the non-aqueous electrolyte comprises a lithium salt, an organic solvent and an additive, the organic solvent comprises fluoroethylene carbonate, and the additive comprises a silane compound containing at least one carbon-carbon double bond: the lithium ion battery satisfies the following conditions: 5≤(S×R) / (F×T)≤35, and 5≤F≤15, 1.4≤R≤1.68, 9≤S≤18, 0.01≤T≤0.5. The lithium ion battery of the present invention can make the lithium ion battery have excellent high-temperature storage performance and high-temperature cycle life while taking into account high energy density by controlling the mass percentage of the organic solvent and the additive in the non-aqueous electrolyte, and controlling the mass percentage of the silicon element in the negative electrode material layer and the compaction density of the negative electrode material layer within a certain range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery with excellent high-temperature storage and high-temperature cycle performance. Background Art

[0002] Lithium-ion batteries have been widely used in smart phones, portable appliances, medical electronics, aerospace, power tools, hybrid vehicles, etc. due to their advantages such as high operating voltage, wide operating temperature range, high output power, no memory effect and long cycle life. With the rapid increase in the demand for battery energy density in various fields, it is urgent to develop lithium-ion batteries with higher energy density.

[0003] At present, the negative electrode used in lithium-ion secondary batteries is mainly carbon-based materials that are advantageous in terms of life and cost of charge and discharge cycles; while silicon-based materials have a higher theoretical capacity than carbon-based materials and can achieve high energy density and are developing rapidly. However, the expansion and contraction of the active materials of the silicon-based negative electrode during the absorption and desorption of lithium ions will lead to a large volume change, causing the SEI film (solid electrolyte intermediate phase) to continuously break and reorganize, and the active material particles to crack during repeated charge and discharge, resulting in the exposure of new active surfaces, which are easy to decompose the electrolyte solvent and thus degrade the cycle characteristics of the battery. And under high temperature conditions, the volume change of the silicon-based negative electrode active material will further increase, resulting in accelerated failure of the lithium-ion secondary battery. In real life, it is difficult to ensure that lithium-ion secondary batteries are at the optimal temperature for a long time when used in power tools and hybrid electric vehicles. Usually, lithium-ion secondary batteries will be at a higher temperature when used for a long time, and the volume change caused by the expansion and contraction of the silicon-based negative electrode active material will further increase, destroying the SEI film on the negative electrode surface or affecting the repair of the SEI film on the negative electrode surface, thereby affecting the service life of the lithium-ion secondary battery.

[0004] Therefore, there is a need to develop secondary lithium-ion batteries that have excellent high-temperature storage and high-temperature cycle performance while achieving high energy density. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a lithium ion battery with excellent high temperature storage and high temperature cycle performance.

[0006] The present invention adopts the following technical solutions:

[0007] A lithium ion battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte;

[0008] The negative electrode comprises a negative electrode material layer comprising a negative electrode active material, wherein the negative electrode active material comprises a silicon-based material;

[0009] The non-aqueous electrolyte includes a lithium salt, an organic solvent and an additive, wherein the organic solvent includes fluoroethylene carbonate, and the additive includes a silane compound shown in structural formula 1:

[0010]

[0011] wherein R1, R2, R3 and R4 are each independently selected from substituted or unsubstituted C1-C5 alkyl, substituted or unsubstituted C2-C5 alkenyl and substituted or unsubstituted C2-C5 alkynyl, and at least one of R1-R4 is selected from substituted or unsubstituted C2-C5 alkenyl;

[0012] The lithium-ion battery meets the following conditions:

[0013] 5≤(S×R) / (F×T)≤35, and 9≤S≤18, 1.4≤R≤1.68, 5≤F≤15, 0.025≤T≤0.5;

[0014] Wherein, S is the mass percentage of silicon element in the negative electrode material layer, in wt%;

[0015] R is the compaction density of the negative electrode material layer, in g / cm 3 ;

[0016] F is the mass percentage of fluoroethylene carbonate in the non-aqueous electrolyte, in wt%;

[0017] T is the mass percentage of the silane compound represented by structural formula 1 in the non-aqueous electrolyte, in wt%.

[0018] The lithium-ion battery of the present invention adopts silicon-based negative electrode materials, which can effectively improve the energy density of the battery, and the higher the content of silicon in the negative electrode active material, the higher the theoretical energy density. However, due to the fact that the volume of silicon in the silicon-based negative electrode active material changes greatly (100-300%) with the insertion and extraction of lithium ions during the charging and discharging process of the lithium-ion battery, it is easy to cause degradation problems such as disconnection of the electronic conduction path in the electrode and micronization of particles. The micronization of particles will cause the exposure of new surfaces with high activity, and its surface will react with the electrolyte to cause the surface of the active material to deteriorate, and under high temperature environment, the reaction between the electrolyte and the surface of the negative electrode active material will become more intense, resulting in problems such as a decrease in the capacity of the active material and a shortened battery life, so it is necessary to control the content of silicon. In addition, the higher the content of silicon in the negative electrode active material, the greater the volume change caused by the insertion / extraction of lithium ions; therefore, while controlling the content of silicon, the compaction density of the negative electrode material layer is adjusted to ensure battery performance. Specifically, as the compaction density of the negative electrode material layer is smaller, the pore structure of the negative electrode material layer is more developed, and the more conducive to the liquid phase conduction of the active particles. Even if the silicon content in the negative electrode active material increases, the negative electrode material layer can withstand the repeated expansion of the battery after multiple charge and discharge. However, if the compaction density is too small, the negative electrode pole piece will peel off and powder will fall off, and the poor electronic conductivity during charging will cause lithium precipitation, which will affect the battery life and reduce the energy density of the battery. Therefore, the present invention controls the silicon content in the negative electrode material layer while regulating the compaction density of the negative electrode material layer. It can reduce the compaction density of the negative electrode material layer while increasing the silicon content, so as to maintain the product (S×R) of the mass percentage S of the silicon element in the negative electrode material layer and the compaction density R of the negative electrode material layer in the negative electrode pole piece relatively stable. Specifically, the mass percentage content S of silicon in the negative electrode material layer is 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt% or any range thereof; preferably, the mass percentage content S of silicon in the negative electrode material layer is 10wt% to 16wt%. The compaction density R of the negative electrode material layer is 1.4g / cm 3 , 1.45g / cm 3 , 1.48g / cm 3 , 1.5g / cm 3 , 1.52g / cm 3 , 1.55g / cm 3 , 1.58g / cm 3 , 1.6g / cm 3 、1.63g / cm 3 , 1.65g / cm 3 、1.68g / cm 3Or any range consisting of the above values; Preferably, the compaction density R of the negative electrode material layer is 1.5g / cm 3 ~1.65g / cm 3 .

[0019] Fluoroethylene carbonate (FEC) can form a solid electrolyte film with good elasticity on the surface of silicon-based negative electrode, effectively connect silicon-based active materials, inhibit its volume change during the charge and discharge process, ensure good contact between particles, significantly improve the capacity retention rate of lithium-ion batteries, and reduce the thickness expansion rate of negative electrode sheets. During the cycle process, when the content of fluoroethylene carbonate is insufficient, the cycle life of the negative electrode containing silicon-based negative electrode active materials will suddenly drop; however, too high a content of fluoroethylene carbonate may lead to an aggravation of the gas production problem of the battery, which will also cause the battery cycle life to decay, and excessive fluoroethylene carbonate will increase the charge exchange impedance of the interface, causing an increase in battery impedance and affecting the electrochemical performance of the battery. Therefore, it is necessary to control the amount of fluoroethylene carbonate added according to the content of silicon in the negative electrode material layer, so as to effectively extend the cycle life of the negative electrode containing silicon-based negative electrode active materials. Specifically, the mass percentage F of fluoroethylene carbonate in the non-aqueous electrolyte is 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt% or any range consisting of the above values; preferably, the mass percentage F of fluoroethylene carbonate in the non-aqueous electrolyte is 6wt% to 12wt%.

[0020] The negative electrode of silicon-based materials is not stable enough, and the side reactions are more and more violent than other systems. The silane compound shown in the structural formula 1 contains unsaturated carbon-carbon double bonds, which can absorb unstable free radicals in the electrolyte, reduce side reactions, and obtain electrons on the surface of the negative electrode to generate organic carbonates to protect the negative electrode; it also forms a film on the positive electrode to protect the battery with good high-temperature performance and inhibit gas production during high-temperature storage. However, similar to fluoroethylene carbonate, an excessive amount of the silane compound shown in the structural formula 1 will cause an increase in battery impedance and affect the electrochemical performance of the battery. Therefore, it is necessary to control the amount of the silane compound shown in the structural formula 1 and the fluoroethylene carbonate. According to the product of the content S of the silicon element in the negative electrode material layer and the compaction density R of the negative electrode material layer (S×R), the content F of fluoroethylene carbonate in the non-aqueous electrolyte and the product of the mass percentage T of the silane compound shown in the structural formula 1 in the non-aqueous electrolyte (F×T) are adjusted to take into account its influence on high-temperature performance and the comprehensive electrochemical performance of the battery. Specifically, the mass percentage T of the silane compound shown in the structural formula 1 in the non-aqueous electrolyte can be but is not limited to 0.025wt%, 0.03wt%, 0.05wt%, 0.07wt%, 0.09wt%, 0.1wt%, 0.12wt%, 0.15wt%, 0.16wt%, 0.18wt%, 0.2wt%, 0.24wt%, 0.25wt%, 0.27wt%, 0.3wt%, 0.35wt%, 0.38wt%, 0.4wt%, 0.42wt%, 0.45wt%, 0.48wt%, 0.5wt% or any range consisting of the above values; preferably, the mass percentage F of the silane compound shown in the structural formula 1 in the non-aqueous electrolyte is 0.05wt% to 0.3wt%.

[0021] Specifically, the value of (S×R) / (F×T) can be but is not limited to 5, 6, 7, 8, 9, 10, 12, 14, 15, 16, 18, 20, 21, 22, 24, 25, 27, 28, 30, 32, 33, 35; preferably, the value of (S×R) / (F×T) is 6 to 30, which can make the lithium-ion battery have high energy density while having excellent high temperature storage performance and high temperature cycle life.

[0022] In some embodiments, in the silane compound shown in structural formula 1, R1, R2, R3 and R4 are each independently selected from substituted or unsubstituted C2-C5 alkenyl and substituted or unsubstituted C2-C5 alkynyl; more preferably, R1, R2, R3 and R4 are each independently selected from substituted or unsubstituted C2-C5 alkenyl.

[0023] In some preferred embodiments, the silane compound shown in the structural formula 1 includes at least one of tetravinylsilane, trivinylethylsilane, divinyldiethylsilane, trivinylethoxysilane, vinyltriethylsilane, trivinylethynylsilane, tetrapropylenesilane, trivinylpropylsilane, tripropylenepropylsilane, dipropylenedipropylsilane, and divinyldipropylsilane. More preferably, the silane compound shown in the structural formula 1 is tetravinylsilane.

[0024] In some embodiments, the silicon-based material includes at least one of a silicon material, a silicon oxide material, a silicon carbon material, and a silicon alloy material.

[0025] In some preferred embodiments, the silicon material is nano-silicon material.

[0026] In some preferred embodiments, the silicon oxide material is SiO x Materials, where 0≤x<2.

[0027] In some preferred embodiments, the silicon-carbon material is a silicon-based material containing silicon and carbon materials, and / or containing SiO y and a silicon-based material of a carbon material, wherein 0≤y<2.

[0028] In some preferred embodiments, the silicon alloy material is a Mg2Si alloy material and / or a Fe2Si alloy material.

[0029] Silicon-based materials have high specific capacity, but their lithium insertion mechanism is very prone to volume expansion, which can lead to rupture and failure of the electrode material; carbon-based materials are more stable than silicon-based materials. In some preferred embodiments, the silicon-based material is selected from silicon-carbon materials. The silicon and carbon of the silicon-carbon material form a complementary relationship. The high specific capacity of the silicon-based material is combined with the cyclic stability of the carbon-based material, which can effectively solve the problem of material expansion failure while taking into account good cyclic performance. More preferably, the silicon-carbon material is a silicon-based material containing silicon oxide and graphite.

[0030] In some embodiments, the organic solvent further comprises at least one of cyclic carbonate, linear carbonate, carboxylate and ether compounds other than fluoroethylene carbonate.

[0031] In some preferred embodiments, the cyclic carbonate includes at least one of ethylene carbonate, propylene carbonate, vinylene carbonate and butylene carbonate.

[0032] In some preferred embodiments, the linear carbonate includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate.

[0033] In some preferred embodiments, the carboxylic acid ester includes at least one of methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, methyl butyrate, methyl isobutyrate, methyl trimethylacetate and ethyl trimethylacetate.

[0034] In some preferred embodiments, the ether compound includes at least one of ethylene glycol dimethyl ether, 1,3-dioxolane and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0035] In some embodiments, the non-aqueous electrolyte further includes an auxiliary additive, and the auxiliary additive includes at least one of a cyclic sulfate compound, a sultone compound, a cyclic carbonate compound, a phosphate compound, a borate compound, and a nitrile compound.

[0036] In some preferred embodiments, the cyclic sulfate ester compound includes at least one of 4-methylvinyl sulfate and propylene sulfate.

[0037] In some preferred embodiments, the sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone, and propenyl-1,3-sultone.

[0038] In some preferred embodiments, the cyclic carbonate compound includes at least one of vinylene carbonate, vinyl ethylene carbonate, methylene carbonate, fluoroethylene carbonate (FEC), trifluoromethylethylene carbonate, bisfluoroethylene carbonate and the compound shown in the following structural formula 2:

[0039]

[0040] In the structural formula 2 shown, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group;

[0041] In some preferred embodiments, the compound represented by structural formula 2 includes at least one of the compounds represented by compounds 2-1 to 2-6 below:

[0042]

[0043] In some preferred embodiments, the phosphate compound includes at least one of tris(trimethylsilyl)phosphate (TMSP), tris(triethylsilyl)phosphate and the compound shown in the following structural formula 3:

[0044]

[0045] In the structural formula 3, R 31 , R 32 , R 33 Each independently selected from a C1-C5 saturated hydrocarbon group, an unsaturated hydrocarbon group, a halogenated hydrocarbon group, -Si(C m H 2m+1 )3, m is a natural number from 1 to 3, and R 31 , R 32 , R 33 At least one of the groups is an unsaturated hydrocarbon group; more preferably, the compound shown in structural formula 3 includes at least one of tripropargyl phosphate, dipropargyl methyl phosphate, dipropargyl ethyl phosphate, dipropargyl propyl phosphate, dipropargyl trifluoromethyl phosphate, dipropargyl-2,2,2-trifluoroethyl phosphate, dipropargyl-3,3,3-trifluoropropyl phosphate, dipropargyl hexafluoroisopropyl phosphate, triallyl phosphate, diallyl methyl phosphate, diallyl ethyl phosphate, diallyl propyl phosphate, diallyl trifluoromethyl phosphate, diallyl-2,2,2-trifluoroethyl phosphate, diallyl-3,3,3-trifluoropropyl phosphate and diallyl hexafluoroisopropyl phosphate.

[0046] In some preferred embodiments, the borate ester compound includes at least one of tris(trimethylsilyl)borate and tris(triethylsilyl)borate.

[0047] In some preferred embodiments, the nitrile compound includes at least one of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile.

[0048] In some embodiments, based on the total mass of the non-aqueous electrolyte as 100%, the content of the auxiliary additive is 0.01wt% to 10wt%. Preferably, the content is 0.1wt%-5wt%; more preferably, the content is 0.1wt% to 2wt%. Specifically, the content of any one of the optional substances in the auxiliary additive can be 0.01%, 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.5%, 5%.

[0049] In some embodiments, the lithium salt includes at least one of LiPF6, LiPO2F2, LiBF4, LiBOB, LiSbF6, LiAsF6, LiCF3SO3, LiDFOB, LiDFOP, LiN(SO2CF3)2, LiC(SO2CF3)3, LiN(SO2C2F5)2, LiN(SO2F)2, LiCl, LiBr, LiI, LiClO4, LiB 10 Cl 10 , LiAlCl4, lithium chloroborane, lithium lower aliphatic carboxylate having 4 or less carbon atoms, lithium tetraphenylborate, and lithium imide.

[0050] In a specific embodiment, the total molar content of the lithium salt is 0.1 mol / L to 4 mol / L. In a preferred embodiment, the total molar content of the lithium salt is 0.5 mol / L - 2.5 mol / L. Specifically, the total molar content of the lithium salt can be 0.5 mol / L, 0.55 mol / L, 0.6 mol / L, 0.65 mol / L, 0.7 mol / L, 0.8 mol / L, 0.85 mol / L, 0.9 mol / L, 0.95 mol / L, 1.0 mol / L, 1.1 mol / L, 1.15 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.45 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, 2.0 mol / L, 2.1 mol / L, 2.2 mol / L, 2.3 mol / L, 2.4 mol / L or 2.5 mol / L.

[0051] In some embodiments, the positive electrode material layer includes a positive electrode material layer containing a positive electrode active material, a positive electrode binder, and a positive electrode conductive agent. The positive electrode active material includes Li 1+x Ni a Co b M’ 1-a-b O 2-y A y , where -0.1 ≤ x ≤ 0.2, 0 < a < 1, 0 ≤ b < 1, 0 < a + b < 1, 0 ≤ y < 0.2, M’ includes one or more of Mn, Al, Sr, Mg, Ti, Ca, Zr, Zn, Si, Fe, Ce, Nb, Ga, Cu, Sn, Cr, W or V, and A includes one or more of S, N, F, B, Cl, Br, and I; specifically, the positive electrode active material includes LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.5 Co 0.2 Mn0.2 Al 0.1 O2、LiNi 0.6 Co 0.1 Mn 0.3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.65 Mn 0.35 O2、LiNi 0.75 Mn 0.25 O2、LiNi 0.7 Co 0.1 Mn 0.2 O2、LiNi 0.8 Co 0.05 Mn 0.15 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.8 Co 0.15 Al 0.05 One or more of O2.

[0052] The positive electrode binder includes polyvinylidene fluoride, copolymers of vinylidene fluoride, polytetrafluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene, copolymers of tetrafluoroethylene-hexafluoropropylene, copolymers of tetrafluoroethylene-perfluoroalkyl vinyl ether, copolymers of ethylene-tetrafluoroethylene, copolymers of vinylidene fluoride-tetrafluoroethylene, copolymers of vinylidene fluoride-trifluoroethylene, copolymers of vinylidene fluoride-trichloroethylene, copolymers of vinylidene fluoride-fluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, thermoplastic resins such as polyethylene and polypropylene; acrylic resin; and one or more of styrene butadiene rubber.

[0053] The positive electrode conductive agent includes one or more of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.

[0054] In some embodiments, the negative electrode further comprises a negative electrode current collector, and the negative electrode material layer is disposed on the surface of the negative electrode current collector. The material of the negative electrode current collector may be the same as that of the positive electrode current collector, which will not be described in detail herein.

[0055] In some embodiments, the negative electrode material layer further includes a negative electrode binder and a negative electrode conductive agent, and the negative electrode active material, the negative electrode binder, and the negative electrode conductive agent are blended to obtain the negative electrode material layer. The negative electrode binder and the negative electrode conductive agent may be the same as the positive electrode binder and the positive electrode conductive agent respectively, and will not be elaborated here.

[0056] In some embodiments, the lithium-ion battery further includes a separator, and the separator is located between the positive electrode and the negative electrode.

[0057] The separator may be a conventional existing separator, which may be a ceramic separator, a polymer separator, a non-woven fabric, an inorganic-organic composite separator, etc., including but not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP, and three-layer PP / PE / PP separators.

[0058] For the lithium-ion battery of the present invention, a silicon-based negative electrode active material is selected, fluorinated ethylene carbonate is used as an organic solvent, and a silane compound having at least one carbon-carbon double bond shown in Structural Formula 1 is used as an additive. By controlling the mass percentages of fluorinated ethylene carbonate and the silane compound shown in Structural Formula 1 in the non-aqueous electrolyte, the capacity retention rate of the battery is improved and gas generation during high-temperature storage is inhibited; at the same time, by controlling the mass percentage of silicon element in the negative electrode material layer and the compaction density of the negative electrode material layer within a certain range, it can not only ensure the insertion / extraction of lithium ions in the negative electrode, but also control the negative electrode compaction density to ensure the battery life; when the lithium-ion battery satisfies the following conditions: 5 ≤ (S × R) / (F × T) ≤ 35, and 5 < F ≤ 15, 1.4 ≤ R ≤ 1.68, 9 ≤ S ≤ 18, 0.01 ≤ T ≤ 0.5, the lithium-ion battery can have excellent high-temperature storage performance and high-temperature cycle life while taking into account high energy density. Detailed implementation manners

[0059] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0060] Embodiment 1

[0061] The preparation method of the lithium-ion battery in this embodiment includes the following steps:

[0062] 1) Preparation of the electrolyte:

[0063] Ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) are mixed in a volume ratio of EC:DEC:EMC=20:30:50, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1.0 mol / L, and then fluoroethylene carbonate (FEC) and tetravinylsilane are added. Based on the total weight of the electrolyte as 100%, the mass percentages of fluoroethylene carbonate (FEC) and tetravinylsilane in the electrolyte are shown in Table 1.

[0064] 2) Preparation of positive electrode:

[0065] The positive electrode active material LiNi was mixed in a mass ratio of 97:1.5:1.5 0.8 Co 0.1 Mn 0.1 O2, conductive carbon black Super-P and binder polyvinylidene fluoride (PVDF), and then disperse them in N-methyl-2-pyrrolidone (NMP) to obtain positive electrode slurry. The slurry is evenly coated on both sides of the aluminum foil, dried, rolled and vacuum dried, and welded with aluminum lead wires using an ultrasonic welder to obtain a positive electrode plate with a thickness of 120-150μm.

[0066] 3) Preparation of negative electrode:

[0067] Silicon-carbon material (a mixture of silicon oxide and graphite, in which the mass percentage of silicon element is 7wt%), conductive carbon black Super-P, binder styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) are mixed in a mass ratio of 94:1.5:3.0:1.5, and then dispersed in deionized water to obtain negative electrode slurry. The slurry is coated on both sides of the copper foil, dried, rolled and vacuum dried, and a nickel lead wire is welded with an ultrasonic welder to obtain a negative electrode plate, the thickness of the plate is between 120-150μm, and the compaction density of the negative electrode material layer is shown in Table 1.

[0068] 4) Battery assembly:

[0069] A separator is placed between the positive plate and the negative plate, and then the sandwich structure consisting of the positive plate, the negative plate and the separator is wound, and then the wound body is flattened and placed in an aluminum-plastic shell, and the aluminum-plastic shell is sealed after welding the pole ears to obtain a battery cell to be injected with liquid.

[0070] In a glove box with a dew point controlled below -40°C, the prepared electrolyte was injected into the battery cell, and the battery was sealed after standing for 1 hour. After sealing, the battery was aged at 45°C for 48 hours.

[0071] Then, the first charge was performed at 45°C hot pressing according to the following steps: 0.05C constant current charging for 3 hours, upper limit voltage 4.0V, pressure 3kg / cc; 0.1C constant current charging for 2 hours, upper limit voltage 4.0V, pressure 5kg / cc; 0.2C constant current charging for 2 hours, upper limit voltage 4.0V, pressure 5kg / cc; 45°C shelving for 48 hours, and then further charged at 0.2C constant current to 4.2V, and discharged at 0.2C constant current to 2.75V.

[0072] Examples 2-25 and Comparative Examples 1-14

[0073] This embodiment and comparative example are used to compare and illustrate the lithium ion battery disclosed in the present invention, including most of the operating steps in the above-mentioned embodiment 1, and the difference is that: based on the total weight of the non-aqueous electrolyte as 100%, the mass percentage of fluoroethylene carbonate and the silane compound shown in structural formula 1 in the non-aqueous electrolyte, the composition of the negative electrode active material, the silicon content in the negative electrode material layer, and the compaction density of the negative electrode material layer are as shown in Table 1.

[0074] Table 1

[0075]

[0076]

[0077] The lithium ion batteries prepared in the examples and comparative examples were subjected to performance tests as follows:

[0078] 1. High temperature storage performance test

[0079] At 25°C, charge the formed battery to 4.2V with 0.5C constant current and constant voltage, and the cut-off current is 0.05C; then discharge it to 2.75V with 1C constant current, record the initial discharge capacity, and then charge it to 4.2V with 0.5C constant current and constant voltage, and the cut-off current is 0.05C. Then store it at full capacity at 45°C for 60 days, discharge it to 2.75V with 1C constant current, measure the battery's retention capacity, and calculate the capacity retention rate of 60 days of high-temperature storage. The calculation formula is as follows:

[0080] Battery capacity retention rate (%) = retention capacity / initial discharge capacity × 100%.

[0081] 2. High temperature cycle performance test

[0082] At 45°C, the formed battery is charged to 4.2V with a 1C constant current and constant voltage, and then discharged to 2.75V with a 1C constant current. After 800 cycles of charge / discharge, the retention rate of the 800th cycle capacity is calculated. The calculation formula is as follows:

[0083] 800th cycle capacity retention rate (%) = (800th cycle discharge capacity / 1st cycle discharge capacity) × 100%.

[0084] (1) The test results of Examples 1-14 and Comparative Examples 1-14 are shown in Table 2.

[0085] Table 2

[0086]

[0087]

[0088] It can be seen from the test results of Examples 1-14 that the lithium-ion battery of the present invention uses silicon-based negative electrode active materials, uses fluoroethylene carbonate as an organic solvent, and uses a silane compound containing at least one carbon-carbon double bond as shown in Structural Formula 1 as an additive. By controlling the mass percentage of fluoroethylene carbonate and the silane compound shown in Structural Formula 1 in the non-aqueous electrolyte, the capacity retention rate of the battery is improved and gas generation during high-temperature storage is suppressed; at the same time, the mass percentage of silicon in the negative electrode material layer and the compaction density of the negative electrode material layer are controlled within a certain range, which can ensure that lithium ions are embedded / de-inserted into / from the negative electrode. The negative electrode compaction density can be controlled to ensure the battery life; when the mass percentage S of silicon element in the negative electrode material layer in the lithium ion battery, the mass percentage F of fluoroethylene carbonate in the non-aqueous electrolyte, the mass percentage T of the silane compound shown in structural formula 1 in the non-aqueous electrolyte, and the compaction density R of the negative electrode material layer meet the following conditions: 5≤(S×R) / (F×T)≤35, and 9≤S≤18, 1.4≤R≤1.68, 5≤F≤15, 0.025≤T≤0.5, the high temperature storage performance and high temperature cycle life of the lithium ion battery can be further improved.

[0089] It can be seen from the test results of Comparative Examples 5-14 that when any one of the mass percentage content S of silicon in the negative electrode material layer of the lithium ion battery, the mass percentage content F of fluoroethylene carbonate in the non-aqueous electrolyte, the mass percentage content T of the silane compound shown in the structural formula 1 in the non-aqueous electrolyte, and the compaction density R of the negative electrode material layer does not meet the specified range, or the value of (S×R) / (F×T) is too large or too small, the lithium ion battery cannot be guaranteed to have good high-temperature storage and high-temperature cycle performance. It can be seen that the mass percentage content S of silicon in the negative electrode material layer, the mass percentage content F of fluoroethylene carbonate in the non-aqueous electrolyte, the mass percentage content T of the silane compound shown in the structural formula 1 in the non-aqueous electrolyte, and the compaction density R of the negative electrode material layer have a strong correlation in improving the high-temperature performance of the battery.

[0090] From the test results of Example 1 and Comparative Examples 1-4, it can be seen that the improvement effect of the high temperature storage and high temperature cycle performance of the lithium ion battery is not good when no additives are used (Comparative Example 1) and other additives are used alone (Comparative Examples 2-4) compared with the addition of the compound shown in Structural Formula 1 (Example 1), indicating that the battery performance improvement mechanism of other additives is different from that of the compound shown in Structural Formula 1. In the system of the present invention, the compound shown in Structural Formula 1 is better than other additives in improving the high temperature performance of the battery.

[0091] (2) The test results of Example 1 and Examples 15-19 are shown in Table 3.

[0092] Table 3

[0093] Group Capacity retention rate after 800 cycles at 45℃ / % Storage at 45℃ for 60 days Capacity retention rate / % Example 1 88.6 89.3 Embodiment 15 87.6 89.2 Example 16 86.3 89.4 Embodiment 17 90.2 87.6 Embodiment 18 86.5 87.3 Embodiment 19 87.3 88.1

[0094] It can be seen from the test results of Example 1 and Examples 15-19 that in the battery system of the present invention, when different types of silane compounds represented by structural formula 1 containing at least one carbon-carbon double bond are used as additives, when the mass percentage S of the silicon element in the negative electrode material layer, the mass percentage F of fluoroethylene carbonate in the non-aqueous electrolyte, the mass percentage T of the silane compound represented by structural formula 1 in the non-aqueous electrolyte, and the compaction density R of the negative electrode material layer meet the corresponding conditions, the high-temperature storage and high-temperature cycle performance of the lithium-ion battery can be improved, indicating that the battery system of the present invention is universal for different compounds represented by structural formula 1.

[0095] (3) The test results of Example 1 and Examples 20-22 are shown in Table 4.

[0096] Table 4

[0097] Group Capacity retention rate after 800 cycles at 45℃ / % Storage at 45℃ for 60 days Capacity retention rate / % Example 1 88.6 89.3 Embodiment 20 85.3 84.6 Embodiment 21 84.2 83.2 Embodiment 22 83.2 81.5

[0098] It can be seen from the test results of Example 1 and Examples 20-22 that in the battery system of the present invention, different silicon-based negative electrode materials are used. When the mass percentage S of the silicon element in the negative electrode material layer, the mass percentage F of fluoroethylene carbonate in the non-aqueous electrolyte, the mass percentage T of the silane compound shown in structural formula 1 in the non-aqueous electrolyte, and the compaction density R of the negative electrode material layer meet the corresponding conditions, the high-temperature storage and high-temperature cycle performance of the lithium-ion battery can be improved, indicating that the battery system of the present invention is universal for different silicon-based negative electrode materials.

[0099] (4) The test results of Example 1 and Examples 23-25 ​​are shown in Table 5.

[0100] Table 5

[0101] Group Capacity retention rate after 800 cycles at 45℃ / % Storage at 45℃ for 60 days Capacity retention rate / % Example 1 88.6 89.3 Embodiment 23 90.3 90.1 Embodiment 24 89.3 89.6 Embodiment 25 89.9 87.3

[0102] It can be seen from the test results of Examples 1 and Examples 23-25 ​​that in the battery system provided by the present invention, the additional addition of additives such as lithium difluorophosphate (LiPO2F2), vinyl sulfate (DTD), vinylene carbonate (VC), etc. can further improve the high-temperature storage and high-temperature cycle performance of lithium-ion batteries, indicating that there is a complementary effect between the compound shown in Structural Formula 1 and other additives.

[0103] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.

Claims

1. A lithium ion battery, characterized in that: including a positive electrode, a negative electrode and a non-aqueous electrolyte; The negative electrode comprises a negative electrode material layer comprising a negative electrode active material, wherein the negative electrode active material comprises a silicon-based material; The non-aqueous electrolyte includes a lithium salt, an organic solvent and an additive, wherein the organic solvent includes fluoroethylene carbonate, and the additive includes a silane compound shown in structural formula 1: wherein R1, R2, R3 and R4 are each independently selected from substituted or unsubstituted C1-C5 alkyl, substituted or unsubstituted C2-C5 alkenyl and substituted or unsubstituted C2-C5 alkynyl, and at least one of R1-R4 is selected from substituted or unsubstituted C2-C5 alkenyl; The lithium-ion battery meets the following conditions: 5≤(S×R) / (F×T)≤35, and 9≤S≤18, 1.4≤R≤1.68, 5≤F≤15, 0.025≤T≤0.5; Wherein, S is the mass percentage of silicon element in the negative electrode material layer, in wt%; R is the compaction density of the negative electrode material layer, in g / cm 3 ; F is the mass percentage of fluoroethylene carbonate in the non-aqueous electrolyte, in wt%; T is the mass percentage of the silane compound represented by structural formula 1 in the non-aqueous electrolyte, in wt%.

2. The lithium-ion battery according to claim 1, characterized in that The lithium ion battery satisfies the following condition: 6≤(S×R) / (F×T)≤30.

3. The lithium-ion battery according to claim 1, characterized in that The mass percentage S of silicon element in the negative electrode material layer is 10wt% to 16wt%.

4. The lithium-ion battery according to claim 1, characterized in that: The mass percentage F of fluoroethylene carbonate in the non-aqueous electrolyte is 6wt% to 12wt%.

5. The lithium-ion battery according to claim 1, characterized in that: The mass percentage T of the silane compound represented by the structural formula 1 in the non-aqueous electrolyte is 0.05 wt % to 0.3 wt %.

6. The lithium-ion battery according to claim 1, characterized in that The compaction density R of the negative electrode material layer is 1.5 g / cm 3 ~1.65g / cm 3 .

7. The lithium-ion battery according to claim 1, characterized in that: The silane compound shown in the structural formula 1 includes at least one of tetravinylsilane, trivinylethylsilane, divinyldiethylsilane, trivinylethoxysilane, vinyltriethylsilane, trivinylethynylsilane, tetrapropylenesilane, trivinylpropylsilane, tripropylenepropylsilane, dipropylenedipropylsilane and divinyldipropylsilane.

8. The lithium-ion battery according to claim 1, characterized in that The silicon-based material includes at least one of a silicon material, a silicon oxide material, a silicon-carbon material and a silicon alloy material; and / or, The silicon material is a nano silicon material; and / or, The silicon oxide material is SiO x Materials, where 0≤x<2; and / or The silicon-carbon material is a silicon-based material containing silicon and carbon materials, and / or containing SiO y and a silicon-based material of a carbon material, wherein 0≤y<2; and / or, The silicon alloy material is a Mg2Si alloy material and / or a Fe2Si alloy material.

9. The lithium-ion battery according to claim 1, characterized in that: The organic solvent further comprises at least one of cyclic carbonate, linear carbonate, carboxylate and ether compounds other than fluoroethylene carbonate; and / or, The cyclic carbonate comprises at least one of propylene carbonate, ethylene carbonate, vinylene carbonate and butylene carbonate; and / or, The linear carbonate comprises at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate; and / or, The carboxylic acid ester comprises at least one of methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, methyl butyrate, methyl isobutyrate, methyl trimethylacetate and ethyl trimethylacetate; and / or, The ether compound includes at least one of ethylene glycol dimethyl ether, 1,3-dioxolane and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

10. The lithium ion battery according to claim 1, characterized in that: The non-aqueous electrolyte further includes an auxiliary additive, wherein the auxiliary additive includes at least one of a cyclic sulfate compound, a sultone compound, a cyclic carbonate compound, a phosphate compound, a borate compound and a nitrile compound; and / or, Based on the total mass of the non-aqueous electrolyte being 100%, the content of the auxiliary additive is 0.01wt% to 10wt%; and / or, The cyclic sulfate ester compound includes at least one of vinyl sulfate, 4-methylvinyl sulfate, and propylene sulfate; and / or, The sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone and propenyl-1,3-sultone; and / or, The cyclic carbonate compound includes at least one of vinylene carbonate, ethylene carbonate, methylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, bisfluoroethylene carbonate and the compound shown in the following structural formula 2: In the structural formula 2 shown, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, a C1-C5 group; and / or, The phosphate compound includes at least one of tris(trimethylsilyl)phosphate, tris(triethylsilyl)phosphate and the compound shown in the following structural formula 3: In the structural formula 3, R 31 , R 32 , R 33 Each independently selected from a C1-C5 saturated hydrocarbon group, an unsaturated hydrocarbon group, a halogenated hydrocarbon group, -Si(C m H 2m+1 )3, m is a natural number from 1 to 3, and R 31 , R 32 , R 33 At least one of them is an unsaturated hydrocarbon group; and / or, The borate compound includes at least one of tris(trimethylsilyl)borate and tris(triethylsilyl)borate; and / or, The nitrile compound includes at least one of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebaconitrile.

Citation Information

Patent Citations

  • Lithium ion battery

    CN114361588A

  • Lithium ion battery

    CN116914253A